Tantangan Pendidikan Islam Zaman Modern - Guci, Alexander; Nurdin, Nurdin; Ajizah, Siti (STAI Asy-Syukriyyah, 2024)
In this era, with all the advances in IT and technology as well as changes in social dynamics, it has brought a number of big challenges to the development of Islamic education in Indonesia. Therefore, a deep understanding of these challenges is the main key to implementing effective solutions in aligning Islamic values ​​with the needs of contemporary developments. This research is qualitative research with priority on literature-based critical analysis. The way to conduct this research is to use the narrative method. In critical studies, understanding the context of the challenges of Islamic education in today's exploitative era. This research aims to analyze phenomena or dynamics from an Islamic perspective and strategic efforts to face these challenges. The research results show that the challenges of Islamic education in the current era include (1) The existence of an approach with a worldly orientation, (2) The influence of social media, (3) New approaches in the field of IT-based Islamic education (4) Technology application-based approaches. The strategies and efforts made to answer the challenges of Islamic education in the current era can be formulated as follows: (1) Instilling the values ​​of Islamic education in a comprehensive manner, (2) Approach to Karimah Moral Education in the younger generation, (3) considering the Islamic education system, (4) Improving the quality of teacher resources with an Islamic character, (4) Adapting to applications and technology.